The actual Situation of Teaching of Catholic Religion in Poland - Wiktorowicz, MSF, Slawomir Andrzej (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
This article focuses most of all in the legal norms that regulate the labor situation of catholic religion teachers that give classes in public schools. Particularly, in a complicated and special way of selecting the teachers, their appointment and discharge, salary for the work they do, as well as in a problematic infringement of some of their fundamental rights.